OWN EXPERIENCES OF ABORTION IN DESCRIPTIONS OF PEOPLE ASSOCIATED IN PRO-CHOICE GROUPS ON FACEBOOK IN POLAND - KULETA, KLEMENTYNA (Society Register, 2020)
A restrictive anti-abortion law is in force in Poland. However, many people terminate pregnancy in cases other than those specified in the Act. Public discourse on this subject is dominated by philosophical and legal issues, and it lacks the voices of those who terminated the pregnancy. Abortion is often presented as a sad necessity, as always difficult or traumatic. I conducted research on describing own abortion experiences by people from Facebook pro-choice groups. 99 respondents who had 102 abortions completed an anonymous online questionnaire. From the material of answers, I selected categories that were used to analyze the results of the study: positive emotions, negative emotions, pregnancy as a burden, good experience, difficulty experience, stigmatization, support. It turned out that the experiences of termination of pregnancy were diverse. Respondents, describing their experiences, discussed topics rarely present in the discourse, such as the fact that abortion can be a good experience.